Technologies of sportification: Practice, theory and co-production of training knowledge in cross-country skiing since the 1950s - Svensson, D. (European Studies in Sports History, 2016)
Elite athletes of today use specialized, scientific training methods and the increasing role of science in sports is undeniable. The scientization process started in endurance sports (e.g. Yttergren 2012, Bourne 2008, Krüger 2006, Svensson 2014, Heggie 2011, Johnson 2009), among them cross-country skiing. This article analyzes how Swedish physiologists and cross-country skiers interacted in the scientization of training methods, focusing on the technologies of sportification that were used. Examples of such technologies are scientific testing, training logs, training camps and training manuals. Material from archives, interviews and earlier research will be studied using theories of bio-power (Foucault 1998) and sportification (e.g. Yttergren 2006, Guttmann 1978). The article concludes that while technologies of sportification could not ensure a rapid rationalization of training methods, these technologies over time became standard features in the training and sportification of cross-country skiing.